2019
DOI: 10.1177/1528083719888674
|View full text |Cite
|
Sign up to set email alerts
|

Solution blown nanofibrous air filters modified with glass microparticles

Abstract: High-pressure drop and lower dust holding capacity reduce the performance of nanofibrous air filters. For that reason, this study was carried out to form filters with high-quality factor and high dust holding capacity, thanks to the glass particle additives. In this study, as an approach to such modifications, fluffy nanofiber webs were produced via solution blowing. Polyamide 6 (PA6) was chosen as the base for the nanofibrous mats, where glass microparticles were embedded as an additive to reduce web solidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Polat et al reported about nanofiber mates of polyamide 6 (PA6) and polyamide with integrated glass microparticles. The filtration efficiency of these nanofiber mates was 99.97% at a pressure drop of 187.3 Pa [ 74 ]. Matulevicius et al’s study showed that the filtration results from PA6/6 8% ( w/vol ) solutions electrospun nanofiber filter media with the smallest fiber diameters between 62–66 nm proved the highest filtration efficiency between 84.9–90.9% [ 75 ].…”
Section: Summary Of the Current Air Filtering Materialsmentioning
confidence: 99%
“…Polat et al reported about nanofiber mates of polyamide 6 (PA6) and polyamide with integrated glass microparticles. The filtration efficiency of these nanofiber mates was 99.97% at a pressure drop of 187.3 Pa [ 74 ]. Matulevicius et al’s study showed that the filtration results from PA6/6 8% ( w/vol ) solutions electrospun nanofiber filter media with the smallest fiber diameters between 62–66 nm proved the highest filtration efficiency between 84.9–90.9% [ 75 ].…”
Section: Summary Of the Current Air Filtering Materialsmentioning
confidence: 99%
“…For 1 gsm nanofiber coated mats, the air permeability values measured according the EN ISO 9237 standard was found to be approximately 42 mm/s. [ 25 ] The nanofibrous layer was produced with a basis weight of 1, 2, and 3 g/m 2 on one side of the fabric. The weight ratio of the nanofibrous webs are 0.5, 1, and 1.5 wt% of CF fabric (200 g/m 2 ) for 1, 2, and 3 g/m 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[24] The SB as a novel technique is one of the most feasible nanofiber production technique with many advantages like high feeding rate (up to 30 ml/h per nozzle for SB, which is around 1 ml/h per nozzle for traditional electrospinning technique), no safety issue due to electrostatic forces, independency from polymer solution properties such as dielectric constant and conductivity. [25] To the best knowledge of authors, there is no study on fracture toughness by interleaving solution blown nanofibers. In this study, the Mode-I fracture toughness of advanced composites was improved by incorporating polyamide-based solutionblown nanofibers onto the plies (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Glass particle doped (up to 5%) solution-blown PA-6 nanofibers of an average fiber diameter of 150–200 nm exhibited an increase in air permeability by 200% when compared with untreated PA6 nanofibers. The untreated and treated PA-6 nanofibers both demonstrated PFE of ~>99% for PM 2.5 , however, the latter reduced the pressure drop almost to 50% than the former [ 67 ]. Very recently, a unique semi-interpenetrating nanofibrous aerogel (IPNFA) structure has been investigated for capturing variety of polydisperse fine particles (PFP) through its sponge-like open-pored hierarchical structure, mimicking loofah [ 68 ].…”
Section: Filtration Of Pms Using Ultrafine Fibersmentioning
confidence: 99%